2018
DOI: 10.3758/s13415-018-00657-0
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the noradrenergic/stress system on perceptual biases for reward

Abstract: Previous research has established a role for the norepinephrine (NE)/stress system in individual differences in biases to attend to reward or punishment. Outstanding questions concern its role in the flexibility with which such biases can be changed. The goal of this preregistered study was to examine the role of the NE/stress system in the degree to which biases can be trained along the axis of valence in the direction of reward. Participants genotyped for a common deletion variant of ADRA2b (linked to altere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 70 publications
1
2
0
Order By: Relevance
“…Fourth, as mentioned previously, inflammation may play an important role in the etiology of depression [44]. The present study, for the first time, reported more profound anti-inflammatory effects of EPA than DHA on microglia M1-induced neuroinflammation, such as EPA decreasing IL-1β, IL-6, TNF-α, but DHA only reducing IL-1β levels in the hippocampus of depression model, which should be taken into account for a better clinical outcome.…”
Section: Discussionsupporting
confidence: 73%
“…Fourth, as mentioned previously, inflammation may play an important role in the etiology of depression [44]. The present study, for the first time, reported more profound anti-inflammatory effects of EPA than DHA on microglia M1-induced neuroinflammation, such as EPA decreasing IL-1β, IL-6, TNF-α, but DHA only reducing IL-1β levels in the hippocampus of depression model, which should be taken into account for a better clinical outcome.…”
Section: Discussionsupporting
confidence: 73%
“…It is worth noting that all of our previous studies on the influence of ADRA2B on attention and subjective perception tapped relatively rapid processes, whereas the effects of biased competition measured here emerged more slowly. Moreover, previous studies measuring effects of the deletion variant on emotional attention and perception engaged subjective judgments of emotional content (Ehlers, Ross, & Todd, 2018), or the relative level of noise overlaid on a visual stimulus (Todd et al, 2015), or rapid engagement of selective attentional prioritization of emotional content (Todd et al, 2013). In contrast, the present study required sustained attention to a neutral stimulus over the course of seconds, and therefore continuous inhibition of distraction by the emotional expression.…”
Section: Discussionmentioning
confidence: 83%
“…It is worth noting that all of our previous studies on the influence of ADRA2B on attention and subjective perception tapped relatively rapid processes, whereas the effects of biased competition measured here emerged more slowly. Moreover, previous studies measuring effects of the deletion variant on emotional attention and perception engaged subjective judgments of emotional content (Ehlers, Ross, & Todd, 2018), or the relative level of noise overlaid on a visual stimulus (Todd et al, 2015), or rapid engagement of selective attentional prioritization of emotional content (Todd et al, 2013). In contrast, the present study required sustained attention to a neutral stimulus over the course of seconds, and therefore continuous inhibition of distraction by the emotional expression.…”
Section: Change Detection Accuracymentioning
confidence: 99%